A Randomized Clinical Trial Comparing the Efficacy and Safety of 2% Versus 4% Chlorohexidine Gluconate for Surgical Preparation of the Vagina. Issue 7 (4th July 2022) - Patnam, Radhika; Askew, Amy L.; Alby, Kevin; Hill, Bravada M.; Willis-Gray, Marcella G.; Wu, Jennifer M.; Geller, Elizabeth J.
Abstract : Importance: There have been no studies comparing 2% and 4% chlorhexidine gluconate (CHX) for vaginal surgical site preparation despite both commonly being used. Objectives: The primary objective was to assess the noninferiority of 2% CHX versus 4% CHX to reduce bacterial contamination rates at 60 minutes after surgical preparation of the vagina. Secondary objectives were to assess differences in colony-forming units and the sensation of postoperative vaginal burning and pain. Study Design: This is a single-blinded randomized controlled trial of women who underwent vaginal prolapse surgery. Study participants were randomized into 2 groups: 2% CHX versus 4% CHX. Two vaginal bacterial cultures were collected: (1) preoperatively before vaginal preparation and (2) intraoperatively at 60 minutes. A questionnaire on vaginal pain and burning was administered preoperatively and postoperatively. For our sample size, assuming that 2% CHX would have double the contamination rate of 4% CHX, 26 participants were needed per group to demonstrate noninferiority. Results: Sixty-one women participated in the study. There were no differences in baseline demographics, length of surgery, or surgical procedures. For our primary outcome, the postpreparation contamination rates were 7% for 2% CHX versus 10% for 4% CHX, with a difference of 3% ( P = 0.52). This difference did meet the criteria for noninferiority. Secondary outcomes were not different between groups. Conclusions: Two percent CHX is noninferior to 4% CHX in reducing vaginal bacterial contamination at 60 minutes after vaginal surgical site preparation, with low rates of postpreparation contamination and vaginal discomfort.